Masyarakat Adat Tangsa di Enrekang Sulawesi Selatan, 2004-2018 - Hamida Hamida; M. Rasyid Ridha; Jumadi Jumadi (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
This study aims to determine the background of the formation of the Tangsa indigenous people, the dynamics of the Tangsa indigenous people, and the function and role of traditional institutions in the Tangsa customary community. The results of this study indicate that the indigenous Tangsa community emerged beginning with the arrival of To Manurung namely Saembona and Tangsilondongna who gave birth to three children namely Takke Buku, Masoang, and Embong Bulan. Over time, there have been many changes, including in the Dutch period, the DI / TII period, and even until now it has changed. Based on the results of the study showed that the Tangsa customary community is an organization within the community that still carries out routine activities including solo signs, tuka signs, massalu nene, and tongkonan ma'rara which are supported by the existence of customary stakeholders in each group as important role holders for the implementation routine in the community. This research uses historical research method which consists of four stages, namely heuristics (collecting data or sources), source criticism consisting of internal and external criticism, interpretation or interpretation of sources and historiography, namely writing history.